Hubungan Gula Darah Puasa dengan Kepatuhan Prolanis - Mahendra Wisnu Wijaya; Arief Budi Yulianti; Rio Dananjaya (UNISBA Press, 2024)
Abstract. Diabetes mellitus is a chronic metabolic disorder characterized by increased glucose levels in the blood. The Indonesian government created a Chronic Disease Management Program or Prolanis. This research uses secondary data in the form of Prolanis attendance lists and lab results. This research uses an analytical observational method with a cross sectional research design. The samples taken were type 2 DM patients who were registered as Prolanis members at the Sekejati Health Center in Bandung City and 58 samples were obtained. The results of this study showed that the majority of patients were compliant in following Prolanis at the Sekejati Health Center in Bandung City (87,20%) but the majority of patients who took Prolanis had uncontrolled fasting blood sugar (74,10%). The results of the analysis test using Fisher exact obtained a p value = 0,323, which means there is no relationship between compliance with Prolanis and blood sugar control in type 2 DM patients who took Prolanis at the Sekejati Community Health Center, Bandung City. Abstrak. Diabetes melitus adalah penyakit gangguan metabolisme yang kronik dengan tanda peningatan kadar glukosa di dalam darah. Pemerintah Indonesia membuat suatu Program Pengelolaan Penyakit Kronis atau Prolanis. Penelitian ini menggunakan data sekunder berupa daftar hadir Prolanis dan hasil lab. Penelitian ini menggunakan metode observasional analitik dengan desain penelitian cross sectional. Sampel yang diambil adalah pasien DM tipe 2 yang terdaftar sebagai anggota Prolanis di Puskesmas Sekejati Kota Bandung dan didapatkan sebanyak 58 sampel. Hasil penelitian ini menunjukan bahwa sebagian besar pasien patuh dalam mengikuti Prolanis di Puskesmas Sekejati Kota Bandung (87,20%) namun sebagian besar pasien yang mengikuti Prolanis memiliki gula darah puasa yang tidak terkendali (74,10%). Hasil uji analisis dengan menggunakan Fisher exact didapatkan nilai p=0,323 yang artinya tidak terdapat hubungan antara kepatuhan mengikuti Prolanis dengan keterkendalian gula darah pada pasien DM tipe 2 yang mengikuti Prolanis di Puskesmas Sekejati Kota Bandung.